A Comparative Analysis of Pyramid Topics in Singaporean and Indonesian Mathematics Textbooks from a Mathematical Literacy Perspective - Fatimah Azzahroh; Ely Susanti; Cecil Hiltrimartin (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2026)
This study aims to compare three mathematics textbooks, namely the Kurikulum Tingkat Satuan Pendidikan (KTSP), Kurikulum Merdeka, and the Singapore textbook (New Discovering Mathematics 2B), on the topic of pyramids from a mathematical literacy perspective. This research employs a descriptive-comparative method, using content analysis, to examine the presentation of materials and problem characteristics in relation to Bloom’s taxonomy and their alignment with the PISA 2018 framework. The findings reveal that the KTSP textbook primarily emphasizes basic concepts and lacks real-world context and a variety of problem types. The Kurikulum Merdeka textbook is beginning to incorporate everyday contexts, although it has not yet fully supported higher-order thinking skills. In contrast, the Singapore textbook demonstrates a more comprehensive approach through effective visualizations, a wider range of cognitive-level problems, and contextual problem-solving tasks aligned with PISA characteristics. These results indicate that textbooks integrating visual representations, meaningful contexts, and diverse problem levels are more effective in fostering students’ mathematical literacy. Therefore, improving textbook design in line with international literacy frameworks is essential for enhancing meaningful mathematics learning.